Increasing the Safety of Healthcare Information Systems through Improved Procurement: Toward a Framework for Selection of Safe Healthcare Systems - Andre Kushniruk, Marie-Catherine Beuscart-Zéphir, Alexis Grzes, Elizabeth Borycki, Ludivine Watbled and Joseph Kannry (ElectronicHealthcare, 2013)
[This article was originally published in Healthcare Quarterly, 13(Sp)] In this article, we describe a framework that we have developed for improving the effectiveness of critical decision-making in selecting information systems. In our framework, we consider system selection in terms of strength of evidence obtained from the testing of candidate systems in order to reduce risk and increase the likelihood of selection and implementation of an effective and safe system. Two case studies, one from a major North American hospital and one from a major European hospital, are presented to illustrate how methods such as usability testing can be applied to improve system selection as well as customization (through early identification of system-organization mismatches and error-prone system features). It is argued that technology-organization fit and consideration of the potential for technology-induced error should be important selection criteria in the procurement process. Here, implications are discussed for the development of improved procurement processes to lead to safer healthcare systems.